Migration and wintering of a declining seabird, the thick-billed murre Uria lomvia, on an ocean basin scale: Conservation implications. (August 2016) - Frederiksen, Morten; Descamps, Sébastien; Erikstad, Kjell Einar; Gaston, Anthony J.; Gilchrist, H. Grant; Grémillet, David; Johansen, Kasper L.; Kolbeinsson, Yann; Linnebjerg, Jannie F.; Mallory, Mark L.; McFarlane Tranquilla, Laura A.; Merkel, Flemming R.; et al.
Abstract: Pelagic seabirds are exposed to an array of potential threats during the non-breeding period, and effective management of these threats on a large scale requires knowledge of which populations winter where. Thick-billed murres ( Uria lomvia ) are emblematic of this conservation challenge, since they breed widely in the circumpolar Arctic, with many declining populations in the Atlantic. Threats facing murres include hunting, oil spills, bycatch and oceanic change influencing prey availability. Previous knowledge of migration pathways was insufficient to estimate the composition of various wintering populations. We collated tracking data (light-based geolocation) of 320 murres from 18 colonies in Canada, Greenland, Iceland, Svalbard and mainland Norway. Data were combined with breeding population counts to estimate the size and composition of wintering populations. The main wintering areas were off Newfoundland and Labrador, off West Greenland, and around Iceland. Winter areas were associated with the interface between High and Low Arctic ocean regimes. There was strong correspondence between wintering area and breeding population status: stable populations breeding in Canada and Northwest Greenland wintered mainly off Canada, whereas declining populations from Svalbard and Iceland wintered mainly off West Greenland and around Iceland. Many populations used distinct post-breeding areas, presumably for moulting; some of these areas were previously unknown. In some populations, there was a clear tendency for females to migrate south earlier than males, which accompany flightless fledglings when they leave the colony. Our study provides a key example of the urgency of coordinated, transoceanic management of vulnerable migratory species such as seabirds. Highlights: Atlantic thick-billed murres winter between Greenland and Canada, and around Iceland Populations wintering in Canadian waters are stable Populations wintering around Iceland and Greenland are declining. In some populations, females migrate south more rapidly than males. Murres use distinct post-breeding areas, presumably to moult.